KOMPARASI HASIL PRESTASI BELAJAR SISWA SEKOLAH DASAR INKLUSI DAN HOMESCHOOLING - Alex Yusron Al Mufti (Jurnal Educative: Journal of Educational Studies, 2018)
This study aims to describe the comparation of student achievement results of Primary School Semai Jepara with Homeschooling Primagama Semarang. Because both institutions have similarities in the category of inclusive schools, which accept all children as students based on quotas. In this study, the learning achievement studied is only the value of the main subjects namely Indonesian, Mathematics, and Natural Sciences. The result of research shows that Indonesian and Mathematics score from Semai Primary School students is superior to Homeschooling Primagama Semarang. However, in the subjects of Natural Sciences, students of Homeschooling Primagama Semarang are superior. In general, the average value of learning achievement of the main subjects obtained the conclusion of SD Semai Jepara is superior to Homeschooling Primagama Semarang. Keywords: achievement, primary school, Homeschooling. Penelitian ini bertujuan untuk mendeskripsikan komparasi hasil prestasi siswa Sekolah Dasar Semai Jepara dengan Homeschooling Primagama Semarang. Karena kedua lembaga tersebut memiliki kesamaan dalam hal kategori sekolah inklusi, yang menerima semua anak sebagai siswa berdasarkan kuota. Dalam penelitian ini, prestasi belajar yang diteliti hanya nilai dari mata pelajaran utama yaitu Bahasa Indonesia, Matematika, dan Ilmu Pengetahuan Alam. Hasil penelitian menunjukkan nilai Bahasa Indonesia rata-rata 91,3 dan Matematika 82 dari siswa Sekolah Dasar Semai lebih unggul dibandingkan Homeschooling Primagama Semarang. Namun pada mata pelajaran Ilmu Pengetahuan Alam, nilai siswa Homeschooling Primagama Semarang lebih unggul dengan rata-rata 83,31. Secara umum nilai rata-rata prestasi belajar mata pelajaran utama diperoleh kesimpulan SD Semai Jepara lebih unggul dibandingkan Homeschooling Primagama Semarang. Kata-kata kunci: prestasi, Sekolah Dasar, Homeschooling.